2017
DOI: 10.1371/journal.pone.0180842
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing to determine the contribution of kinase receptor transactivation to G protein coupled receptor signalling in vascular smooth muscle cells

Abstract: G protein coupled receptor (GPCR) signalling covers three major mechanisms. GPCR agonist engagement allows for the G proteins to bind to the receptor leading to a classical downstream signalling cascade. The second mechanism is via the utilization of the β-arrestin signalling molecule and thirdly via transactivation dependent signalling. GPCRs can transactivate protein tyrosine kinase receptors (PTKR) to activate respective downstream signalling intermediates. In the past decade GPCR transactivation dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 96 publications
0
20
0
1
Order By: Relevance
“…Microarrays and RNAseq provide an alternative approach to more holistically capture how GPCR activation changes the cell. Such approaches show that GPCR signaling can activate the transcription of hundreds of genes 39,62–64 . As a point of comparison, activation of RTKs can induce changes to the transcription of ~1,000 genes 65–67 .…”
Section: A “Cellular Perspective” Of Gpcr Signaling: Phosphoproteomicmentioning
confidence: 99%
“…Microarrays and RNAseq provide an alternative approach to more holistically capture how GPCR activation changes the cell. Such approaches show that GPCR signaling can activate the transcription of hundreds of genes 39,62–64 . As a point of comparison, activation of RTKs can induce changes to the transcription of ~1,000 genes 65–67 .…”
Section: A “Cellular Perspective” Of Gpcr Signaling: Phosphoproteomicmentioning
confidence: 99%
“…We previously found that the GPCR agonist thrombin transactivates the EGFR and TGFBR1 to stimulate the expression of enzymes involved in the hyperelongation of glycosaminoglycan chains on the proteoglycan, biglycan ( 123 , 124 ) which is associated with increased lipid retention in the vessel wall initiating atherosclerosis ( 125 , 126 ). We have described that GPCR transactivation of either receptor is occurring via completely different mechanisms and the identification of a common mechanism can attenuate all GPCR-mediated GAG chain elongation ( 127 , 128 ). However, established data for GPCR transactivation of PTKRs and newly emerging data for mechanisms of S/TKRs indicates that ROS may be involved in both transactivation mechanisms and as such ROS would represent the first common mechanism and hence the first potential target to prevent all transactivation signalling.…”
Section: Discussionmentioning
confidence: 99%
“…QuAdTrim was first developed in 2011 for use in a metagenomic study that utilised Illumina paired end sequence data (Ross, et al, 2012). Subsequently QuAdTrim has been used for quality control of Illumina sequence data in from human, bacterial, virus, cattle, sheep, and salmon studies amoung others (Bolormaa, et al, 2019;Daetwyler, et al, 2017;Kamato, et al, 2017;Kijas, et al, 2019;Kijas, et al, 2018;Wei, et al, 2018).…”
Section: History Usage and Future Directionsmentioning
confidence: 99%